Methods in psychological research - Rooney, Bryan J.; Evans, Annabel (SAGE Publications, Inc., 2019)
Methods in Psychological Research introduces students to the rich world of research in psychology through student-friendly writing, compelling real-world examples, and frequent opportunities for practice. The Fourth Edition equips students with the tools they need to understand research concepts, conduct their own experiments, and present their findings.